Treatment outcomes and validation of the stopping rule for response to peginterferon in chronic hepatitis B: A Thai nationwide cohort study - Phunchai Charatcharoenwitthaya (2018)
© 2016 Journal of Gastroenterology and Hepatology Foundation and John Wiley & Sons Australia, Ltd Background and Aims: Peginterferon has demonstrated effectiveness in clinical trials in patients with chronic hepatitis B (CHB). However, its efficacy in real-life settings remains unclear. We investigated the efficacy of peginterferon for CHB and validated the performance of previously identified response predictors in clinical practice. Methods: We analyzed prospectively collected data from a Thai nationwide cohort of CHB patients treated with peginterferon alfa-2a (180 µg/week, 48 weeks). Results: Among a total of 233 patients, mostly with genotype B or C, sustained response was observed in 23% of 135 hepatitis B e antigen (HBeAg)-positive patients (HBeAg seroconversion with hepatitis B virus [HBV] DNA < 2000 IU/mL) and 42% of 98 HBeAg-negative patients (HBV DNA < 2000 IU/mL with aminotransferase normalization) at 24 weeks after treatment. Age, sex, presence of cirrhosis, genotype, and pretreatment levels of aminotransferase, HBV DNA, and hepatitis B surface antigen (HBsAg) were not identified as significant predictors of sustained response. In HBeAg-positive patients, HBsAg > 20 000 IU/mL at week 12 provided a good stopping rule, with a negative predictive value of 96%. In HBeAg-negative patients, the performance of 12-week stopping rules of no decline in HBsAg with a < 2log10 decline in HBV DNA and a < 10% log10 decline in HBsAg showed modest negative predictive values of 80% and 66%, respectively, for achieving sustained response. Conclusion: Outcomes in CHB patients treated with peginterferon in a clinical setting are similar to those demonstrated in clinical trials. Application of the early stopping rule based on HBsAg quantification may allow individualization of therapy, particularly in HBeAg-positive patients.